ATYPICAL REVERSE REACTION IN A MULTIBACILLARY PATIENT - Gabriel Monteiro de Castro Chaves; Amanda Cohn Serra; Luiza Ferreira d'Almeida; José Augusto da Costa Nery (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Leprosy is an infectious disease caused by Mycobacterium leprae that primarily affects the skin and/or peripheral nerves. It can have periods of acute reactions known as type 1 or reverse and type 2 or erythema nodosum. These reactions reflect the immune-mediated inflammatory process involving different mechanisms of hypersensitivity. The type 1 reaction corresponds to a sudden increase in cell-mediated immunity is more common in paucibacillary forms of the disease and type 2 reaction is recognized as changes in humoral immunity, is more common in multibacillary. This article aims to demonstrate a case of reverse reaction in a multibacillary patient. KEYWORDS – Leprosy, multibacillary; Mycobacterium leprae.